Family Resemblances between Contemporary Post-Subjectivist Philosophy and Animistic Religions - Luks, Leo; Moor, Argo (Problemos, 2016)
Criticism of the Cartesian subject and attempts at establishing a post-subjectivist philosophy are prevalent in contemporary continental philosophy. People living in modern Western cultures are frequently characterized as residing in a permanent state of identity crisis. The question “who comes after the subject?” is topical both in philosophy and in the daily life of Western people. In this interdisciplinary study, we argue that that there are considerable family resemblances between the aims of post-subjectivist philosophy and animistic religions. We will first provide the requisite background for understanding the animistic treatment of subjectivity by describing three principles: the Principle of Unity, the Principle of Balance, and Complementary Polar Thinking. These principles further develop our treatment of the concept of network thinking, as outlined in our previous joint paper, “Networks and Hierarchies: Two Ways of Thinking”. We will then compare the animistic treatment of subjectivity with current critiques of the subject. Although we will not express a normative request for the resurrection of animism, we nonetheless cannot exclude the possibility that the study of animistic principles may provide local solutions to the postmodern crisis of the subject.